Meat subtypes and colorectal cancer risk: A pooled analysis of 6 cohort studies in Japan. Issue 11 (26th September 2019) - Islam, Zobida; Akter, Shamima; Kashino, Ikuko; Mizoue, Tetsuya; Sawada, Norie; Mori, Nagisa; Yamagiwa, Yoko; Tsugane, Shoichiro; Naito, Mariko; Tamakoshi, Akiko; Wada, Keiko; Nagata, Chisato; et al.
Abstract: Red meat and processed meat have been suggested to increase risk of colorectal cancer (CRC), especially colon cancer. However, it remains unclear whether these associations differ according to meat subtypes or colon subsites. The present study addressed this issue by undertaking a pooled analysis of large population‐based cohort studies in Japan: 5 studies comprising 232 403 participants (5694 CRC cases) for analysis based on frequency of meat intake, and 2 studies comprising 123 635 participants (3550 CRC cases) for analysis based on intake quantity. Study‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using the Cox proportional hazards model and then pooled using the random effect model. Comparing the highest vs lowest quartile, beef intake was associated with an increased risk of colon cancer in women (pooled HR 1.20; 95% CI, 1.01‐1.44) and distal colon cancer (DCC) risk in men (pooled HR 1.30; 95% CI, 1.05‐1.61). Frequent intake of pork was associated with an increased risk of distal colon cancer in women (pooled HR 1.44; 95% CI, 1.10‐1.87) for "3 times/wk or more" vs "less than 1 time/wk". Frequent intake of processed red meat was associated with an increased risk of colon cancer in women (pooled HR 1.39; 95% CI, 0.97‐2.00; P trend = .04) for "almost every day" vs "less than 1 time/wk". No association was observed for chicken consumption. The present findings support that intake of beef, pork (women only), and processed red meat (women only) might be associated with a higher risk of colon (distal colon) cancer in Japanese. Abstract : As shown in figure A and figure B, comparing the highest versus lowest quartile, beef intake was associated with an increased risk of colon cancer in women (pooled HR 1.20, 95% CI 1.01‐1.44) and distal colon cancer (DCC) risk in men (pooled HR 1.30, 95% CI 1.05‐1.61). Figure C shows that frequent intake of pork was associated with an increased risk of DCC in women (pooled HR 1.44, 95% CI 1.10‐1.87) for "3 times/week or more" versus "<1time/week". Figure D shows that frequent intake of processed red meat was associated with an increased risk of colon cancer in women (pooled HR 1.39, 95% CI 0.97‐2.00; p‐trend=0.04) for "almost every day" versus "<1 time/week".